Students' perception regarding the integration of English-subtitled films in language learning - Siahaan, Safnidar; Eriyanti, Ribut Wahyu; Rofieq, Ainur; Huda, Atok Miftahul (Universitas Riau Kepulauan, 2024)
This research underscores the extensive use of films as a powerful strategy in English language learning, emphasizing its manifold advantages. Films, by offering authentic language input and exposure to diverse content, significantly enhance language proficiency, fostering a holistic grasp of vocabulary, accents, and language structures. The combined application of films with effective instructional strategies positively influences language awareness and facilitates vocabulary expansion, aligning seamlessly with contemporary pedagogical approaches that prioritize cultural competences and inclusivity. The immersive nature of films contributes to the development of various language skills, encompassing vocabulary enrichment, enhanced listening comprehension, and improved writing proficiency. This unique quality positions films as valuable mediums for interdisciplinary teaching, enriching educational experiences and fostering inclusivity within academic environments. The study used qualitative method, specifically a Likert scale questionnaire, and found that most students believed that watching English-subtitled movies improves their conversational English skills, makes learning more fun, and enhances classroom learning. However, other students remained neutral on specific issues, indicating differing perspectives. Overall, students had favorable experiences with movies, including enjoyment, perceived language improvement, and practical use in daily conversations.